PERANCANGAN TAMPILAN WEB DESIGN TOKO GRAND CENTRAL BUKITTINGGI - FATLINA AULIA, Dr. Budiwirman, M.Pd, Drs. Ariusmedi, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Toko Grand Central is a clothing store that sells clothes from children to adult clothing, located at Bukittinggi. Grand Central store was established on 11 July 2012. The store founded by Hj. Eli Hartati. Located at Jln. ST. Syahrir 34 Tarok Dipo Bukittinggi. Since Toko Grand Central stands, campaign carried out only through flyers and word of mouth. That is way the design of web interface design Toko Grand Central Bukittinggi made.he purpose of this design is to inform the target audience about Toko Grand Central, so it can be recognized by the public, especially Bukittinggi’s people.The method of data analysis in the design used SWOT analysis which analyzes the advantages, weaknesses opportunities and threats that exist in Toko Grand Central.The result achieved is to design a media campaign that is easy to understand and be understood by the target audience, so that the message can be conveyed to the target audience and the target audience chose Toko Grand Central to shop..Keywords: Web Design, Promotion, Toko Grand Central.